Geotrilha: Jogo didático para o ensino e aprendizagem de geografia no ensino fundamental - Argenta, Gustavo (2024)
This study reports on the development, application, and analysis of an educational game for teaching and learning geography content in the 6th grade of elementary school. The general aim of this research was to contribute to the teaching and learning of Geography through the development and application of an educational game. The specific objectives were to develop a board game for teaching and learning the basic concepts of Geography; to apply the didactic game with a 6th grade class; and to analyze the quality of the material developed and the participation of the students in the class with the didactic game. The qualitative-quantitative approach was used as the method of analysis to observe the results from two conceptions, the qualitative and the quantitative. In order to obtain the results, the students who participated in the process answered four questionnaires, whose aim was to understand the students' relationship with games, check their development in relation to Geography and assess their individual thoughts on the game Geotrilha: a trilha dos conceitos geográficos, a product developed from this research. It was possible to observe the students' affinity with games, which related their daily lives to the practice carried out in the research. The students enjoyed playing Geotrilha and said they would like to have more lessons involving games, and it was possible to observe learning processes based on lessons using the game. The conclusion is that it is possible to learn using games and that Geotrilha influenced the students' relationship with the subject.